House prices, disposable income and permanent and temporary shocks: The NZ, UK and US experience - Fraser, Patricia; Hoesli, M.; McAlevey, L. (Emerald Group Publishing Ltd., 2012)
Purpose: The purpose of this paper is to compare responses of house prices in three important markets when faced with permanent and temporary shocks to income. It additionally decomposes each historical house price series into its permanent, temporary and deterministic components. Design/methodology/approach: Using quarterly data over 1973-2008, two-variable systems of house prices and income are specified for three major house-owning economies: New Zealand (NZ), the United Kingdom (UK) and the United States of America (USA). Findings: NZ and UK housing markets are sensitive to both permanent and temporary shocks to income, while the US market reacts to temporary shocks with the permanent component having a largely insignificant role to play in house price composition. In NZ, the temporary component of house prices has tended to be positive over time, pushing prices higher than they would have been otherwise; while in the UK, both permanent and temporary components have tended to reinforce each other. Originality/value: The paper uses state-of-the-art methods to analyse the relationships between income and house prices in three economies.